Hermeneutical Backlash: Trans Youth Panics as Epistemic Injustice - George, B. R.; Goguen, Stacey (Feminist Philosophy Quarterly, 2021)
In this paper we use the contemporary example of trans youth panics to introduce the notion of hermeneutical backlash, in which defenders of an established, unjust hermeneutical regime actively work to undermine and discredit hermeneutical liberation. We argue that the strategies and tropes of the trans youth panic illustrate a general propaganda vulnerability of epistemic liberation movements (including familiar examples from recent history), and so are troubling for reasons that go beyond their application to trans youth. This exploration of a few specific cases of hermeneutical liberation and hermeneutical backlash calls attention to the need for further theoretical work on the dynamics of struggles for (and against) hermeneutical justice.
Keywords: approches et analyses; backlash herméneutique; cours; cycles supérieurs; discipline; discours dominant; discours médiatique; enfants trans*; fem9000; histoire et politique; hétérosexisme; injustices herméneutiques; militance; philosophie; philosophie féministe; sciences humaines; systèmes d'oppressions; thématiques; transphobie; violences

Epistemic Decolonization as Overcoming the Hermeneutical Injustice of Eurocentrism - Posholi, Lerato (Philosophical Papers, 2020)
This paper is broadly concerned with the question of what epistemic decolonization might involve. It is divided into two parts. The first part begins by explaining the specifically epistemic problem to which calls for epistemic decolonization respond. I suggest that calls for decolonization are motivated by a perceived epistemic crisis consisting in the inadequacy of the dominant Eurocentric paradigm to properly theorize our modern world. I then discuss two general proposals, radical and moderate, for what epistemic decolonization might involve. In the second part, I argue that the inadequacy of Eurocentric epistemic resources constitutes a hermeneutical injustice caused by an irreducible form of epistemic oppression. I then argue that addressing this form of epistemic oppression requires thinking ‘outside’ of the Eurocentric paradigm because the paradigm might fail to reveal and address the epistemic oppression sustaining it. This lends further plausibility to the radical proposal that epistemic decolonization must involve thinking from ‘outside’ the Eurocentric paradigm, but also accommodates the moderate proposal that adopting critical perspectives on Eurocentric thought is an important part of epistemic decolonization.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; décolonisation épistémique; fem9000; féminisme décolonial; injustices herméneutiques; injustices épistémiques; philosophie; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences; études décoloniales

Je suis un monstre qui vous parle: rapport pour une académie de psychanalystes - Preciado, Paul B. (Grasset, 2020)
« La psychanalyse est face à un choix historique sans précédent : soit elle continue à travailler avec l'ancienne épistémologie de la différence sexuelle et légitime de facto le régime patriarco-colonial qui la soutient, devenant ainsi responsable des violences qu'elle produit, soit elle s'ouvre à un processus de critique politique de ses discours et de ses pratiques. Continuer à pratiquer la psychanalyse en utilisant la notion de différence sexuelle, avec des instruments cliniques comme le complexe d'OEdipe, est aussi aberrant que de prétendre la terre plate. Le temps est venu de sortir les divans sur les places, collectiviser la parole, politiser les corps, débinariser la sexualité et décoloniser l'inconscient : la survie de la psychanalyse est à ce prix. »– Quatrième de couverture.
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; discours dominant; fem7000; identités LGBTQIA2+; patriarcat; personnes trans*; sciences humaines; systèmes d'oppressions; thématiques; violences; épistémologie

On Epistemic Appropriation - Davis, Emmalon (Ethics, 2018)
In this article, I offer an account of an unjust epistemic practice―namely, epistemic appropriation―that harms marginalized knowers through the course of conceptual dissemination and intercommunal uptake. The harm of epistemic appropriation is twofold. First, while epistemic resources developed within the margins gain uptake with dominant audiences, those resources are overtly detached from the marginalized knowers responsible for their production. Second, epistemic resources developed within, but detached from, the margins are utilized in dominant discourses in ways that disproportionately benefit the powerful.
Keywords: approches et analyses; appropriation épistémique; cours; cycles supérieurs; discipline; discours dominant; droits des personnes; fem9000; injustices épistémiques; inégalités; philosophie; privilèges; rapports de pouvoir; savoirs des marges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Epistemic Exploitation - Berenstain, Nora (Ergo, an Open Access Journal of Philosophy, 2016)
Epistemic exploitation occurs when privileged persons compel marginalized persons to educate them about the nature of their oppression. I argue that epistemic exploitation is marked by unrecognized, uncompensated, emotionally taxing, coerced epistemic labor. The coercive and exploitative aspects of the phenomenon are exemplified by the unpaid nature of the educational labor and its associated opportunity costs, the double bind that marginalized persons must navigate when faced with the demand to educate, and the need for additional labor created by the default skepticism of the privileged. I explore the connections between epistemic exploitation and the two varieties of epistemic injustice that Fricker (2007) identifies, testimonial and hermeneutical injustice. I situate epistemic exploitation within Dotson’s (2012; 2014) framework of epistemic oppression, and I address the role that epistemic exploitation plays in maintaining active ignorance and upholding dominant epistemic frameworks.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; exploitation épistémique; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; oppression épistémique; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; travail; violences; éthique

Normal life: Administrative violence, critical trans politics, and the limits of law - Spade, Dean (Duke University Press, 2015)
Attendez—qu'est-ce qui ne va pas avec les droits ? On suppose généralement que les personnes transgenres et non conformes au genre devraient suivre les stratégies de droits civils et «d'égalité» des organisations de défense des droits des lesbiennes et des homosexuels en faisant campagne pour des réformes juridiques qui garantiraient ostensiblement la non-discrimination et une protection égale devant la loi. Cette approche suppose que la meilleure façon de lutter contre la pauvreté et la criminalisation qui affligent les populations trans est d'obtenir une reconnaissance légale et une inclusion dans les institutions de l'État. Mais cette stratégie est-elle efficace ? Dans la vie normaleDean Spade présente des critiques révélatrices du cadre d'égalité juridique pour le changement social et pointe des exemples d'activisme trans populaire transformateur qui soulève des demandes qui vont au-delà des réformes traditionnelles des droits civiques. Spade explose les hypothèses sur ce que les droits légaux peuvent faire pour les populations marginalisées et décrit les processus et les formations de résistance transformatrice qui s'attaquent aux causes profondes du mal et de la violence. Dans la nouvelle postface de cette édition révisée et augmentée, Spade note l'intégration rapide de la politique trans et constate que ses prédictions selon lesquelles l'obtention d'une reconnaissance légale ne profitera pas aux populations trans se concrétisent. Spade examine les efforts récents de l'administration Obama et des défenseurs de l'égalité des trans pour "pinkwash" la violence d'État en articulant les systèmes militaires et pénitentiaires américains comme des sites pour les réformes d'inclusion des trans. Dans le contexte de la récente visibilité accrue des personnes trans et de la politique trans, Spade continue de plaider pour le démantèlement des systèmes de violence d'État qui raccourcissent la vie des personnes trans. Aujourd'hui plus que jamais, Normal Life est un appel urgent à la justice et à la libération trans, et aux transformations radicales que cela nécessitera.
https://public.ebookcentral.proquest.com/choice/publicfullrecord.aspx?p=2096555
Keywords: amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; droit; fem9000; identités LGBTQIA2+; militance; personnes trans*; ressource en ligne; régions géographiques; science politique et droit; systèmes d'oppressions; thématiques; violences; états-unis